2022
DOI: 10.1108/cr-12-2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

ESG and performance in public health-care companies: the role of disclosure and director liability

Abstract: Purpose The seepage of companies' capital accommodated by weak country-level institutions is inconducive to building sustainable businesses. Companies' performance on environmental, social and governance (ESG) issues is still a challenging question. This study aims to test the predictability of ESG on the performance of the health-care industry from a global perspective, while accounting for the country disclosure and director liability indices and performing robustness tests. Design/methodology/approach Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The relationship between managerial characteristics and CSR was investigated in the study of Theiri and Alareeni (2022), which found a positive relationship between managerial characteristics and CSR under certain financial constraints related to the size and indebtedness level. The aim of the El Khoury et al (2022b) study 2022 was to test the impact of ESG on the performance of the health-care industry. This study used a sample of 912 companies operating in 38 different countries during the period from 2012 to 2020.…”
Section: Lecturer and Special Issue Reviewmentioning
confidence: 99%
“…The relationship between managerial characteristics and CSR was investigated in the study of Theiri and Alareeni (2022), which found a positive relationship between managerial characteristics and CSR under certain financial constraints related to the size and indebtedness level. The aim of the El Khoury et al (2022b) study 2022 was to test the impact of ESG on the performance of the health-care industry. This study used a sample of 912 companies operating in 38 different countries during the period from 2012 to 2020.…”
Section: Lecturer and Special Issue Reviewmentioning
confidence: 99%
“…There will be enormous possibilities for the growth and development of the Indian healthcare sector due to expanding GDP in absolute terms and rising GDP expenditure on healthcare (Rastogi and Sharma 2020). The attribute of ESG is pointed out due to the impact of sustainability on healthcare FP (El Khoury et al 2022). The study by Kalia and Aggarwal (2022) examines the outcome of ESG scores on FP of healthcare companies of 33 nations using the variables, i.e., ROA and ROE.…”
Section: Introductionmentioning
confidence: 99%
“…Streamlining sustainability reporting across the industries and policy regulations by integrating national sustainability goals and United Nations Sustainable Development Goals Disclosures, as well as creating the necessary ecosystem for uplifting the ESG disclosures, which helps the Indian companies perform better in financial and non‐financial performance. It is the need of the hour to study the quantum of the relation between ESG and firm performance to a larger extent (Clark & Viehs, 2014; El Khoury et al, 2022). The findings of the prior studies on ESG disclosures and firm performance are very meager.…”
Section: Introductionmentioning
confidence: 99%
“…Again, in 2015, SEBI increased the number of listed companies from 100 to 500 to submit the BRR. Finally, following the deliberation by SEBI, BRR was replaced with Business and firm performance to a larger extent (Clark & Viehs, 2014;El Khoury et al, 2022). The findings of the prior studies on ESG disclosures and firm performance are very meager.…”
mentioning
confidence: 99%